The Role and Function of Regulatory T Cells in Toxoplasma gondii-Induced Adverse Pregnancy Outcomes - Xuyang Gao; Yue Zhong; Yifan Liu; Runmin Ding; Jinling Chen (Journal of Immunology Research)
Infection with Toxoplasma gondii (T. gondii) during the pregnant period and its potentially miserable outcomes for the fetus, newborn, and even adult offspring continuously occur worldwide. People acquire infection through the consumption of infected and undercooked meat or contaminated food or water. T. gondii infection in pregnant women primarily during the gestation causes microcephaly, mental and psychomotor retardation, or death. Abnormal pregnancy outcomes are mainly associated with regulatory T cell (Treg) dysfunction. Tregs, a special subpopulation of T cells, function as a vital regulator in maintaining immune homeostasis. Tregs exert a critical effect on forming and maintaining maternal-fetal tolerance and promoting fetal development during the pregnancy period. Forkhead box P3 (Foxp3), a significant functional factor of Tregs, determines the status of Tregs. In this review, we summarize the effects of T. gondii infection on host Tregs and its critical transcriptional factor, Foxp3.